Issues in Routing Mechanism for Packets Forwarding: A Survey - Rohit Nilkanth Devikar; Dipak V. Patil; V. Chandraprakash (Institute of Advanced Engineering and Science, 2016)
Nowadays internet has become more popular to each and every one. It is very sensitive to nodes or links failure due to many known or unknown issues in the network connectivity. Routing is the important concept in wired and wireless network for packet transmission. During the packet transmission many times some of the problems occur, due to this packets are being lost or nodes not able to transmit the packets to the specific destination. This paper discusses various issues and approaches related to the routing mechanism. In this paper, we present a review and comparison of different routing algorithms and protocols proposed recently in order to address various issues. The main purpose of this study is to address issues for packet forwarding like network control management, load balancing, congestion control, convergence time and instability. We also focus on the impact of these issues on packet forwarding.